Fabrication and Characterization of Electrospun Dopants/PS Composite Fibers with Porous and Hollow‐Porous Structures. Issue 5 (25th February 2016) - Tian, Lidong; Gu, Junwei; Lei, Xingfeng; Lv, Zhaoyuan; Qiao, Mingtao; Yin, Changjie; Zhang, Qiuyu
Abstract : Electrospun dopants/PS composite fibers with hollow‐porous and multichannel hollow‐porous structures are fabricated from PS sol in one step. Compared to porous fibers obtained from PS solution, the fabricated sol‐electrospinning PS fibers present a larger multi‐stage degree of interfacial structure and diversity in the internal environment. Abstract : Three different dopants are used to fabricate electrospun dopants/polystyrene (dopants/PS) composite fibers from PS solution and PS sol. The relative humidity and the influence of the dopants on the morphologies, diameter, porous structures, and dopant distribution of electrospun PS fibers are investigated. Compared to those obtained from PS solution, electrospun dopants/PS composite fibers from PS sol with hollow‐porous and multichannel hollow‐porous structures present significant advantages due to the multi‐stage degree of interfacial structure and diversity of the internal environment. In comparison to coaxial electrospun PS fibers, the electrospun dopants/PS composite fibers from PS sol obtained in one step have an improved yield and a simplified technological process simultaneously, leading to significant competitiveness in fields such as catalysis, fluidics gas storage, and sensing.